Peran Kepala Sekolah dalam Pelaksanaan Peningkatkan Mutu Lulusan - Fatchurrochman, Fatchurrochman; Wuryandini, Endang; Abdullah, Ghufron (Jurnal Indonesia Sosial Sains, 2022)
Effective schools can be seen from the quality of graduates with supporting components including school principals, teachers, staff, curriculum, implementation of learning, facilities and infrastructure, learning tools and resources, monitoring learning, evaluation of learning and school climate. The quality of graduates is the fulfillment of certain criteria accepted by customers, in this case the world of work and education. Improving the quality of graduates is an effort carried out to improve the quality of graduates through improving the quality of teachers, students, learning systems (curriculum) and facilities and infrastructure. This study aims to describe the role of school principals in improving the quality of graduates. This study uses descriptive qualitative research methods, data collection methods by interview, observation and documentation. The place where this research was conducted was at SMK Negeri 1 Kedungwuni, Pekalongan Regency. Interviews, observations and documentation were used for data collection techniques. The results of the study show that the implementation of improving the quality of graduates is carried out through strategies and policies as well as programs prepared by school principals through improving the quality of teachers, learning, facilities and infrastructure as well as strengthening partnerships with the business world and the industrial world. The conclusions obtained from this study indicate that the implementation of improving the quality of graduates of building modeling and information design skills competency is successful.